Design features that reduce the use of seclusion and restraint in mental health facilities: a rapid systematic review. Issue 7 (7th July 2021) - Oostermeijer, Sanne; Brasier, Catherine; Harvey, Carol; Hamilton, Bridget; Roper, Cath; Martel, Andrew; Fletcher, Justine; Brophy, Lisa
Abstract : Increasing efforts are being made to prevent and/or eliminate the use of seclusion and restraint in mental health facilities. Recent literature recognises the importance of the physical environment in supporting better outcomes in mental health services. This rapid review scoped the existing literature studying what physical design features of mental health facilities can reduce the use of seclusion and physical restraint. Design: A rapid review of peer-reviewed literature. Methods: Peer-reviewed literature was searched for studies on architectural design and the use of restraint and seclusion in mental health facilities. The following academic databases were searched: Cochrane Library, Medline, PsycINFO, Scopus and Avery for English language literature published between January 2010 and August 2019. The Joanna Briggs Institute's critical appraisal tool was used to assess the quality of included studies. Results: We identified 35 peer-reviewed studies. The findings revealed several overarching themes in design efforts to reduce the use of seclusion and restraint: a beneficial physical environment (eg, access to gardens or recreational facilities); sensory or comfort rooms; and private, uncrowded and calm spaces. The critical appraisal indicated that the overall quality of studies was low, as such the findings should be interpreted with caution. Conclusion: This study found preliminary evidence that the physical environment has a role in supporting the reduction in the use of seclusion and restraint. This is likely to be achieved through a multilayered approach, founded on good design features and building towards specific design features which may reduce occurrences of seclusion and restraint. Future designs should include consumers in a codesign process to maximise the potential for change and innovation that is genuinely guided by the insights of lived experience expertise.